Off-label use of 0.4 % sodium hyaluronate teardrops: a safe and effective solution for submucosal injection in gastric endoscopic submucosal dissection - Arantes, Vitor; Aliaga Ramos, Josue; Abdul Rani, Rafiz; Yoshida, Naohisa (Endoscopy International Open, 2020)
Background and study aims Submucosal (SM) injection is a critical step in endoscopic submucosal dissection (ESD). In Japan, use of viscous solutions such as sodium hyaluronate are recommended; the commercially product available is MucoUp (Seikagaku Co. and Boston Scientific Japan Co., Japan). Nevertheless, MucoUp is expensive and unavailable in many Western countries. For the past 8 years, we have been using low-cost sterile teardrops solution composed of 0.4 % sodium hyaluronate (Adaptis Fresh, Legrand Laboratory, Brazil). This solution is readily available in drugstores with a cost of approximately US$ 10.00 for each 10-cc bottle. The aim of this study was to present the clinical outcome with off-label sodium hyaluronate use for SM injection in gastric ESD.Patients and methods A single-center retrospective study of collected data investigating consecutive patients that underwent gastric ESD between 2012 and 2019. ESD was performed using 0.4 % sodium hyaluronate teardrop for SM injection and Flush Knife BT 2.5 (Fujifilm Co., Japan). The following data were analyzed: clinical-pathological features, en-bloc, R0 and curative resection rate, procedure duration, adverse events, and clinical outcome.Results ESD was performed with sodium hyaluronate for submucosal injection in 78 patients. The en-bloc resection rate and R0 resection rate were 96.1 % and 92.3 %, respectively. The curative resection rate for epithelial lesions was 83.8 %. Adverse events occurred in 5 cases (6.3 %): delayed bleeding (3.8 %, 3 cases) and perforation (2.5 %, 2 cases); all managed successfully by clipping and thermal coagulation. The mean volume of sodium hyaluronate solution used per patient was 10 cc (SD: ± 8 cc). During follow-up (mean: 17 months; SD: ± 14.5 months), two patients developed metachronous lesions (2.5 %).Conclusions Off-label use of teardrops with 0.4 % sodium hyaluronate for submucosal injection was demonstrated to be safe and able to provide an effective submucosal cushion that facilitates SM dissection in gastric ESD procedures.